2017
DOI: 10.1063/1.4997768
|View full text |Cite
|
Sign up to set email alerts
|

A study of evolution of residual stress in single crystal silicon electrode using Raman spectroscopy

Abstract: Silicon is a promising anode material for lithium ion batteries. However, lithiation of silicon generates stress that is known to be the primary reason for the failure of the anode. This study explored the existence of residual stress in single crystalline silicon electrodes after full de-lithiation, i.e., under no mechanical or electrical load. The magnitude of residual stress and its evolution with the number of lithiation-delithiation cycles is measured by Raman spectroscopy and a simple mechanics based app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, the starting powder has also a slight shift compared to the theoretical band positions. It probably has its origin in impurities [ 41 ] or/and residual stresses [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the starting powder has also a slight shift compared to the theoretical band positions. It probably has its origin in impurities [ 41 ] or/and residual stresses [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the starting powder has also a slight shift compared to the theoretical band positions. It probably has its origin in impurities [41] or/and residual stresses [42]. However, Figure 10c,d shows that the TiN phase tempered under a nitrogen atmosphere also undergoes some recrystallization (compare Figure 3e).…”
Section: Of 19mentioning
confidence: 99%
“…One year later, Jana and co-workers studied the evolution of the stress generated in a single c-Si during lithiation which was the main cause of failure and fracture of these NIBAMs. 145 They demonstrated that in situ Raman was an ideal tool to understand the progressive failure mechanism of single c-Si anodes. Whilst Cabo-Fernandez and co-workers used Raman to investigate the (de)lithiation mechanism on carbon-coated ZnFe2O4 (ZFO) anode 146 which is a TMO-based NIBAM type.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Up to now, no consensus about the aging mechanisms has been achieved yet. In contrast to the enormous work on particle-based anodes, much less research was done using single crystalline silicon electrodes, although it is a well-defined model electrode [28][29][30][31][32][33][34] . Single-crystal silicon allows us to study the lithiation process in a system without any binder or conductive agent.…”
mentioning
confidence: 99%
“…Operando neutron and X-ray reflectometry reveal the depth-dependent lithium concentration over several cycles, but no fractures were observed due to experimental limitations [32][33][34] . The mechanical stress within the (100) silicon was determined by Chon et al depending on the cell voltage 29 , whereas Jana et al elucidated the cycle-dependent change of the residual stress within the (100) Si-crystal 28 . An ex-situ electron microscopy study revealed cracking of (100) silicon after several cycles 30 , whereas the crack propagation depends on the crystal orientation 31,35 .…”
mentioning
confidence: 99%